Profile of maternal deaths in a city in southern Brazil: an ecosystem perspective (Research, Society and Development, 2020)
To analyze the profile of maternal deaths that occurred in Rio Grande / RS between the years 2013 to 2017 from an ecosystem perspective. Descriptive, exploratory study with a quantitative approach. Data collected in the 1st semester of 2018, in investigation forms of maternal deaths that occurred in the period from 2013 to 2017 present in the Health Department and in medical records of two hospital institutions in the city of Rio Grande. For analysis, simple statistical analysis was used. All maternal deaths (n = 9) were characterized by age between 30 to 39 years (n = 4), white (n = 5), living in the urban area (n = 9), single (n = 4), users of the Unified Health System (n = 6). Deaths occurred in hospitals (n = 4), in the puerperal period (n = 4), classified as obstetric maternal death from direct causes (n = 6). The unique profile of maternal deaths occurring in the ecosystem under study makes it possible to direct actions aimed at the specificities of this space, such as improving relations and mutual influences between the elements of the ecosystem.